(NsOBRANIE SO^INENIJ W DWENADCATI TOMAH(B; s (NpOWESTI I RASSKAZY (B/ s (N~ASTX (B2s - (NdOSTOEWSKIJ(B, (NfEDORs ((NmOSKWA(B: s (NpRAWDA(B, s, 1982)
(NwO WTOROJ TOM WO[LI PROIZWEDENIQ(B: "(NdQD@[KIN SON(B", "(NsELO sTEPAN^IKOWO I EGO OBITATELI(B", "(NsKWERNYJ ANEKDOT(B", "(NzAPISKI IZ PODPOLXQ(B", "(NkROKODIL(B".s
rus
Keywords: (NpOWESTI I RASSKAZYs